2016
DOI: 10.1371/journal.pone.0161735
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Cycle Influences Spontaneous Delivery in Cows

Abstract: There is a popular belief that the lunar cycle influences spontaneous delivery in both humans and cattle. To assess this relationship, we investigated the synodic distribution of spontaneous deliveries in domestic Holstein cows. We used retrospective data from 428 spontaneous, full-term deliveries within a three-year period derived from the calving records of a private farm in Hokkaido, Japan. Spontaneous birth frequency increased uniformly from the new moon to the full moon phase and decreased until the wanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
2
16
1
1
Order By: Relevance
“…Here, lunar cycle and weather conditions were investigated to test whether they were associated with DCF or preterm calving in Japanese Black cows. These variables were chosen because the lunar cycle has been reported to be associated with calving frequency in Holstein dairy cows [6] and with birth rates in humans [15], and weather conditions were also associated with calving frequency in beef cows [7]. To assess the effect of those variables on DCF and preterm calving, our research used two studies; one for each day level and the other for cow levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, lunar cycle and weather conditions were investigated to test whether they were associated with DCF or preterm calving in Japanese Black cows. These variables were chosen because the lunar cycle has been reported to be associated with calving frequency in Holstein dairy cows [6] and with birth rates in humans [15], and weather conditions were also associated with calving frequency in beef cows [7]. To assess the effect of those variables on DCF and preterm calving, our research used two studies; one for each day level and the other for cow levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lunar data were also derived from data reported by the Japanese Meteorological Agency. The eight phases of the lunar cycle were categorized in accordance with a previous study [6]: new moon to waxing crescent (Lunar 1); waxing crescent to first quarter (Lunar 2), first quarter to waxing gibbous (Lunar 3), waxing gibbous to full moon (Lunar 4), full moon to waning gibbous (Lunar 5), waning gibbous to last quarter (Lunar 6), last quarter to waning crescent (Lunar 7), and waning crescent to new moon (Lunar 8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moon phases have been reported to increase the number of deliveries in cows [ 32 ]. The same authors would report that apart from the higher birth rates of the dairy cows near and during the full moon, the predicted and real delivery dates significantly differed within the eight moon phases.…”
Section: Discussionmentioning
confidence: 99%
“…In birds and cows, for example, daily changes in melatonin and corticosterone are lost during the days of the full moon. It has been suggested that the secretion of neurohormones may be triggered by electromagnetic radiation and/or the gravitational force of the moon [11][12][13].…”
Section: The Effect Of the Moon And Planets On The Biological Clockmentioning
confidence: 99%